Síntesis de compuestos heterocíclicos de potencial actividad citostática en las células meristemáticas de allium cepa l. a partir de derivados de aminopirazoles - Saavedra Suárez, Segundo Francisco (2014)
The aim of this study was to investigate the synthesis of new heterocyclic compounds from 5-amino-1-phenyl-3-methyl-pyrazole with ethyl acetoacetate, acetylacetone and p-dimethylaminobenzaldehyde in ratios of 1: 1 and 2: 1 to determine the cytostatic effect of new heterocyclic compounds rootlets meristem cells of Allium cepa L. Product of the synthesis the following compounds obtained 1-phenyl-3,6-dimethyl-pyrazolo [3,4-b] pyridin-4-one, 1-phenyl-3-methyl-5- (p-dimethylamino-benzylideneamino ) - pyrazole, 1-phenyl-3, 4,6-trimethyl-pyrazolo [3,4-b] pyridine. To determine the cytostatic effect tests were carried out in rootlets of Allium cepa L (onion). A each experimental unit was assigned a volume of 200 ml to 0.1% of heterocyclic obtained respectively. It was compared to a control group. The 1-phenyl-3,6-dimethyl-pyrazolo compounds [3,4-b] pyridin-4-one and 1-phenyl-3, 4,6-trimethyl-pyrazolo [3,4-b] pyridine showed no action cytostatic against the meristematic cells of Allium cepa L. (onion). The compound 1-phenyl-3-methyl-5- (p-dimethylamino-benzylideneamino) - pyrazole, if presented action cytostatic.